Materiały ze schyłku okresu halsztackiego i starszego okresu przedrzymskiego ze stanowiska Smólsk 1, powiat włocławski - Piotrowska, Magdalena; Kot, Karolina (Acta Universitatis Lodziensis. Folia Archaeologica, 2011)
A multicultural site of Smólsk 1, Włocławek commune was subjected to a rescue archaeological excavation prior to the construction of the A1 motorway. Archaeological investigations were conducted by a team from the Foundation of the University of Lodz. An area of 2,37 ha has been excavated, and 618 features were recorded. In the area of segment C relics of a cloche grave cemetery were discovered, on which 11 graves were registered, clearly concentrated in the south. All the burials are individual graves without structures or kerbstones. Among them there were 9 cloche graves, 1 pit grave, and 1 urn grave. An observed element of the funeral ritual is covering the urn and cloche with the remains of the stake. Grave goods included fragments of urns and cloches, a swan-neck pin and occasional burnt fragments of preserved bronze and glass decorations. The pottery represented typical forms characteristic of cemeteries of the Cloche Graves culture. On the grounds of an anthropological analysis it has been determined that the dead were young individuals. Three female burials and 2 male ones were identified, in the other cases the sex was undetermined. Settlement finds were recorded on the entire site. A clear concentration of the pits was registered about 100 m to the west from the above described cemetery. These features did not disturb the cemetery space, and were located on its circuit, sometimes at a considerable distance. 63 features have been identified, including post-holes, pits and the remains of a building. On the grounds of the artifacts obtained both from the cemetery and from the settlement objects, the period of use of the complex corresponds to HaD and the older pre-Roman period.